Thermal history and behavioural plasticity shape reef fish tolerance to marine heatwaves - Angus Mitchell; Sean D. Connell; Ben P. Harvey; Sylvain Agostini; Jeffrey Jolly; Guinther Mitushasi; Timothy Ravasi; David J. Booth; Ivan Nagelkerken (Coral Reefs, 2026)
Marine heatwaves are becoming more frequent and intense, driving mass fish mortalities and reshaping marine ecosystems, yet the capacity of fishes to tolerate heatwaves remains unclear. We quantified physiological condition and behavioural responses of juvenile warm-water ( Abudefduf vaigiensis ) and cool-water ( Microcanthus strigatus ) fishes from three natural climate analogues—an ambient temperate reef, an ocean warming analogue, and a combined warming and extreme acidification analogue—before and during the 2023 global marine heatwave, and under a + 3 °C simulated heatwave in the laboratory. In the laboratory, warm-water fish from the warm reef began the experiment in leaner condition than cool reef fish but increased their bite rates under heatwave conditions, compensating for elevated metabolic demand and maintaining body condition. Cool-water fish showed no behavioural adjustment to the heatwave, and body condition diverged by reef origin: cool reef fish lost weight across all treatments while warm- and extreme-origin fish maintained condition, suggesting tolerance was conferred by prior thermal history rather than acute behavioural responses. In the field, warm-water fish were leaner and had lower protein content during the 2023 heatwave than before it, while cool-water fish from the extreme reef had lower body condition than those from the cool reef prior to the heatwave. Our findings suggest that behavioural plasticity can facilitate warm-water fish tolerance to heatwaves at their cold leading edges, while thermal history supports heatwave tolerance in cool-water fish within their core ranges. Populations inhabiting naturally extreme climate analogues may therefore harbour pre-adapted, climate-resilient fish in a future ocean.

Marine invertebrates and fishes exhibit inconsistent body size responses to ocean acidification - Mary E. Hart; Sean D. Connell; Angus Mitchell; Ben P. Harvey; Sylvain Agostini; Joshua M. Heitzman; Ivan Nagelkerken (Limnology and Oceanography, 2026)
Body size is a fundamental characteristic of all living organisms that determines physiological functions and life‐history traits. Ecological theory predicts that ocean acidification can cause body size reductions, confirmed by several studies reporting miniaturization in ectotherms. Based on this prediction, we would expect a broad suite of species to show similar plastic body‐size responses to elevated CO 2 . Using four natural climate change analogues of ocean acidification across the northern and southern hemispheres, we quantified body size alterations across 18 marine invertebrate and fish taxa to test for climate‐driven miniaturization. Only three species consistently showed body‐size reductions under ocean acidification: one urchin and two fish species. In contrast, 15 other species, ranging from highly calcified to non‐calcified, displayed unchanged or increased body sizes or inconsistent miniaturization. If body‐size miniaturization responses were consistently reproducible across taxa we would have observed it more frequently, suggesting that species responses to ocean acidification are more variable than previously thought and likely vary depending on a species' physiology and life history. Thus, rather than entire communities undergoing miniaturization, species are likely to display a spectrum of responses, with some exhibiting size reductions, others demonstrating physiological resistance to elevated CO 2 , and others potentially benefiting from the indirect effects of ocean acidification.

Natural Analogues of Climate Change Can Reveal Fish Responses Across Multiple Levels of Biological Organisation - Chloe Hayes; Angus Mitchell; Timothy Ravasi; Ivan Nagelkerken (Fish and Fisheries, 2026)
Anthropogenic climate change is threatening ecosystem functionality and biodiversity globally. While significant research has been dedicated to understanding how organisms may respond to future climate change, most of these studies focus on individual levels of biological organisation in controlled laboratory settings, which often fail to capture the complexity of natural ecosystems. Organisms respond to climate stressors across various levels of biological organisation, which also involve complex interactions or feedback mechanisms among levels, making it difficult to generalise responses to climate change from laboratory experiments or single levels alone. Natural analogues provide a unique opportunity to observe complex ecological interactions in real‐world environments with long‐term exposure to climate change stressors. Here, we provide a systematic literature review to reveal how natural analogues of ocean warming and ocean acidification can be used to assess fish responses to climate change across multiple levels of biological organisation (from molecular to biogeographical scales) and to assess how cross‐level buffering and feedback mechanisms may shape fish species persistence in a future ocean. We identify key knowledge gaps and propose research frameworks that integrate natural analogues with laboratory experiments, mesocosms, and predictive models to better capture the complexity of fish responses to climate stressors in a more holistic way. Finally, we highlight the importance of coordinated, cross‐system research using multiple natural analogues to reveal adaptive mechanisms and strengthen predictions of fish community reorganisation under climate change.

Marine Heatwaves, Ocean Warming and Acidification Reshape Reef Fish Gut Microbiomes - Angus Mitchell; Chloe Hayes; Callum J. Hudson; Sean D. Connell; Ben P. Harvey; Sylvain Agostini; Jeffrey Jolly; Timothy Ravasi; David J. Booth; Ivan Nagelkerken (Molecular Ecology, 2026)
Extreme climatic events and gradual climate change are increasingly anticipated to interact and reshape ecological communities. However, the combined effects of ocean warming, acidification and marine heatwaves on host‐associated microbial communities and their potential role in host adaptation remain poorly understood. Here, we assessed shifts in gut microbiome communities and their associations with physiological performance in one tropical ( Abudefduf vaigiensis ) and one subtropical ( Microcanthus strigatus ) reef fish species, across three temperate reefs representing natural analogues of climate change: a present‐day baseline (‘cool reef’), a chronically warmed reef (‘warm reef’) and a reef experiencing combined warming and extreme acidification (‘extreme reef’). We also examined gut microbiome changes in A. vaigiensis before and during a severe marine heatwave. A. vaigiensis had lower gut microbiome evenness and diversity at the warm (43% and 44% decrease, respectively) and extreme (38% and 31% decrease) reefs compared to the cool reef, and its gut microbiome community shifted at the extreme reef with a 122% increase in abundance of opportunistic bacteria Vibrio . A. vaigiensis also had lower gut microbiome richness at the warm (42% decrease) and extreme (52% decrease) reefs during the heatwave compared to pre‐heatwave individuals. In contrast, M. strigatus showed higher microbiome evenness (99% increase) and diversity (98% increase) at the warm reef compared to the cool reef; however, these gains were lost at the extreme reef, with microbiome diversity and evenness returning to cool reef levels. Microbiome changes in both species were generally not associated with their physiological performance (protein content, oxidative stress, antioxidant capacity or body condition). Our findings suggest that marine heatwaves, ocean warming and acidification can reshape reef fish gut microbiomes, driving simplification in Abudefduf vaigiensis but distinct restructuring in Microcanthus strigatus . We conclude that climate‐driven microbiome reshuffling may alter host–microbiome relationships and functions in fishes in a future ocean.

Range‐extending fish become competitive dominants under ocean warming but not heatwaves or acidification - Angus Mitchell; Ericka O. C. Coni; Sean D. Connell; David J. Booth; Ben P. Harvey; Sylvain Agostini; Timothy Ravasi; Ivan Nagelkerken (Ecology, 2026)
Ocean warming is driving species range extensions into cooler regions. The direct physiological influence of warming on species performance can accelerate such extensions into novel ecosystems; however, indirect effects of invader–resident interactions in cooler regions may counter these positive effects. Here, we examined the foraging performance and densities of competing warm‐water and cool‐water fishes across a latitudinal temperature gradient spanning 1500 km from tropical to temperate reefs subjected to rapid ocean warming in the southern hemisphere, and across natural analogs of temperate, tropicalized, and acidified reef localities in the northern hemisphere, and during a severe marine heatwave at a temperate reef. While current levels of ocean warming have allowed the warm‐water fish to extend their ranges into temperate ecosystems at both hemispheres, their foraging performance was reduced at both the cold‐ and warm‐temperate reefs compared to the (sub)tropical reefs. However, at the (warmer) tropicalized reef, the warm‐water fish had higher foraging performance and maintained densities, even under extreme pH reduction, compared to the temperate reef. In contrast, the cool‐water species struggled at the warmer tropicalized and extreme reefs with reduced foraging performance and lower population densities compared to the temperate reef. Contrastingly, the severe heatwave experienced at the temperate reef did not alter the foraging behaviors of either species. We suggest that ocean warming boosts the foraging performance of the range‐extending warm‐water fish and impairs that of their cool‐water competitor at temperate reefs, irrespective of acidification and heatwaves, leading to a shift in dominance hierarchies on temperate reefs. We conclude that warming‐driven increases in foraging performance of the warm‐water species may alleviate foraging limitations and enhance its establishment at its leading range edges under climate change, to the detriment of its cool‐water competitors.

Stomach Microbiome Simplification of a Coral Reef Fish at Its Novel Cold‐Range Edge Under Climate Change - Chloe Hayes; Angus Mitchell; Roger Huerlimann; Jeffrey Jolly; Chengze Li; David J. Booth; Timothy Ravasi; Ivan Nagelkerken (Molecular Ecology, 2025)
Climate‐driven range extensions of animals into higher latitudes are often facilitated by phenotypic plasticity. Modifications to habitat preference, behaviour and diet can increase the persistence of range‐extending species in novel high‐latitude ecosystems. These strategies may be influenced by changes in their gut and stomach microbial communities that are critical to host fitness and potentially adaptive plasticity. Yet, it remains unknown if the gut and stomach microbiome of range‐extending species is plastic in their novel ranges to help facilitate these modifications. Here, we categorised stomach microbiome communities of a prevalent range‐extending coral reef fish along a 2000‐km latitudinal gradient in a global warming hotspot, extending from their tropical core range to their temperate cold range edge. At their cold range edge, the coral reef fish's stomach microbiome showed a 59% decrease in bacterial diversity and a 164% increase in the relative abundance of opportunistic bacteria ( Vibrio ) compared to their core range. Microbiome diversity was unaffected by fish body size, water temperature, physiology (cellular defence and damage) and habitat type (turf, barren, oyster, kelp and coral) across their range. The observed shifts in microbiome composition suggest dysbiosis and low plasticity of tropical range‐extending fishes to novel environmental conditions (e.g., temperate prey and lower seawater temperature) at their novel range edges, which may increase their susceptibility to disease in temperate ecosystems. We conclude that fishes extending their ranges to higher latitudes under ocean warming can experience a simplification (i.e., reduced diversity) of their stomach microbiome, which could restrict their current rate of range extensions or establishment in temperate ecosystems.

Extreme iron cycling in a coastal lake-lagoon system driven by interactions between climate and entrance management - Scott G. Johnston; Thor Aaso; Damien T. Maher; Edward D. Burton; Mitchell Call; Mathew Birch; John Schmidt; Angus Ferguson (Science of The Total Environment, 2024)

Novel ecological interactions alter physiological responses of range-extending tropical and local temperate fishes under ocean warming - Minami Sasaki; Angus Mitchell; David J. Booth; Ivan Nagelkerken (Science of The Total Environment, 2024)

Correction to: Projected ocean acidification and seasonal temperature alter the behaviour and growth of a range extending tropical fish - Angus Mitchell; Chloe Hayes; David J. Booth; Ivan Nagelkerken (Coral Reefs, 2024)

Projected ocean acidification and seasonal temperature alter the behaviour and growth of a range extending tropical fish - Angus Mitchell; Chloe Hayes; David J. Booth; Ivan Nagelkerken (Coral Reefs, 2023)
Climate-driven invasions of ecosystems by range-extending animals are often mediated by behavioural modifications that increase their chances of establishment in foreign biological communities. This creates novel ecological interactions that can affect the behaviour of native species in recipient ecosystems. However, this question has seldom been addressed in marine systems, in particular with the additive effect of ocean acidification and the mediating effects of seasonal climate variability. Here, we performed a laboratory experiment to evaluate how novel species interactions, ocean acidification, and projected future summer versus winter temperatures could affect the behaviour and growth of a range-extending tropical and co-shoaling temperate fish. Compared to current-day summer temperatures, tropical fish became 4% more active, 90% more aggressive, and increased their growth rates (standard length: +42%) during future summers in their novel poleward ranges, but reduced their aggression by 64%, boldness by 52%, feeding by 45% and growth rates (wet weight: −70%, standard length: −26%) during future winters compared to current-day summer temperatures. Additionally, tropical fish became 3% more active under ocean acidification compared to no ocean acidification. Conversely, temperate fish behaviour was unaffected by climate treatments but their growth rates were > 200% faster under future winter versus current and future summer temperatures. We conclude that projected future winter conditions in temperate ecosystems may reduce the performance of range-extending fishes in temperate fish communities and slow down tropicalisation of higher latitudes.

Future shock: Ocean acidification and seasonal water temperatures alter the physiology of competing temperate and coral reef fishes - Angus Mitchell; Chloe Hayes; David J. Booth; Ivan Nagelkerken (Science of The Total Environment, 2023)

Ocean warming and acidification degrade shoaling performance and lateralization of novel tropical–temperate fish shoals - Angus Mitchell; David J. Booth; Ivan Nagelkerken (Global Change Biology, 2022)
Gregarious behaviours are common in animals and provide various benefits such as food acquisition and protection against predators. Many gregarious tropical species are shifting poleward under current ocean warming, creating novel species and social interactions with local temperate taxa. However, how the dynamics of these novel shoals might be altered by future ocean warming and acidification remains untested. Here we evaluate how novel species interactions, ocean acidification and warming affect shoaling dynamics, motor lateralization and boldness of range‐extending tropical and co‐shoaling temperate fishes under controlled laboratory conditions. Fishes were exposed to 1 of 12 treatments (combinations of three temperature levels, two p CO 2 levels and two shoal type levels: mixed species or temperate only) for 38 days. Lateralization (a measure of asymmetric expression of cognitive function in group coordination and predator escape) of tropical and temperate species was right‐side biased under present‐day conditions, but side bias significantly diminished in tropical and temperate fishes under ocean acidification. Ocean acidification also decreased shoal cohesion irrespective of shoaling type, with mixed‐species shoals showing significantly lower cohesion than temperate‐only shoals irrespective of climate stressors. Tropical fish became bolder under ocean acidification (after 4 weeks), and temperate fish became bolder with increasing temperature, while ocean acidification dampened temperate fish boldness. Our findings highlight the direct effect of climate stressors on fish behaviour and the interplay with the indirect effects of novel species interactions. Because strong shoal cohesion and lateralization are key determinants of species fitness, their degradation under ocean warming and acidification could adversely affect species performance in novel assemblages in a future ocean, and might slow down tropical species range extensions.

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Growth Recovery of Lemna gibba and Lemna minor Following a 7-Day Exposure to the Herbicide Diuron - Mitchell Burns; Mark L. Hanson; Ryan S. Prosser; Angus N. Crossan; Ivan R. Kennedy (Bulletin of Environmental Contamination and Toxicology, 2015)

Double primary cancers of the breast and thyroid in women: molecular analysis and genetic implications - Tuya Pal; Nancy Hamel; Danny Vesprini; Kevin Sanders; Margot Mitchell; Nada Quercia; Nathalie Ng Cheong; Angus Murray; William Foulkes; Steven A. Narod (Familial Cancer, 2001)